Academic publication activities and perspectives of rheumatology practitioners in the COVID-19 pandemic - Abdulvahap Kahveci; Alper Gümüştepe; Nurhan Güven; İsmihan Sunar and Şebnem Ataman (Archives of Rheumatology, 2023)
Objectives: This study aimed to analyze the research, publication activities, and perspectives on clinical practices of rheumatology practitioners during the coronavirus disease 2019 (COVID-19) pandemic. Materials and methods: The survey-based cross-sectional study was designed online and included 24 closed-ended questions. After performing a pilot test and validation of survey, it was conducted among clinicians between September 2021 and December 2021. Results: One-hundred fifteen clinicians (54 males, 61 females; 78.1% in rheumatology practice for at least five years) responded to the survey. The respondents indicated that they worked in coronavirus-related departments, comprising inpatient service (50.4%), consultancy (42.6%), and outpatient clinic (27.8%). Around 40% of clinicians stated they spent less time on scientific research (43.1%) and clinical learning activities (43.2%), while almost the same proportion of them spent more (41.1% and 45.0%, respectively). This study revealed that 53.5% published at least one paper covering mostly COVID-19 in the scientific citation index (SCI) or SCI-expanded (SCI-E) indexed journals. However, nearly half of them did not have any papers published in the SCI/SCI-E (46.5%) or non-SCI/SCI-E indexed (44.6%) journals. Regarding the perspectives of clinicians about clinical practices, they considered fewer biological (57.0%) and nonbiological (55.0%) drug usage, reported fewer outpatient clinic visits (88.2%), more newly diagnosed rheumatic diseases (62.5%), and more disease exacerbations (31.2%). Most of the clinicians (range, 76.2 to 86.3%) thought they accurately managed their patients during the COVID-19 pandemic. Conclusion: Clinicians published mostly coronavirus-related papers in the pandemic era, and in the self-assessment, clinicians thought that they correctly manage their patients. In addition, this study reflected the frequency of academic publications and clinicians’ work routines during the pandemic.